2008
DOI: 10.1002/sia.2860
|View full text |Cite
|
Sign up to set email alerts
|

Extracting information on the surface monomer unit distribution of PLGA by ToF‐SIMS

Abstract: The surface chemistry of a range of random poly l-lactide-co-glycolide (PLGA) materials has been investigated using XPS, static secondary ion mass spectrometry (SSIMS) and gentle secondary ion mass spectrometry (G-SIMS). The estimated mole fraction of lactide units provided by SSIMS was in good agreement with bulk composition and appeared not to have been affected by contamination. Conversely, XPS assessment of lactide compositions was unreliable due to hydrocarbon contamination contributions. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Figure 6(a) shows three peaks that correspond to the two polymers in the blend. [29][30][31][32] The first peak, located at 284.4 eV, was assigned to the C-C group, the second peak at 286.4 eV was attributed to the C-O group, and the third peak at 288.7 eV was attributed to C ¼ O bond. However, in Figure 6(b) an additional peak was observed.…”
Section: Xps and Ftirmentioning
confidence: 99%
“…Figure 6(a) shows three peaks that correspond to the two polymers in the blend. [29][30][31][32] The first peak, located at 284.4 eV, was assigned to the C-C group, the second peak at 286.4 eV was attributed to the C-O group, and the third peak at 288.7 eV was attributed to C ¼ O bond. However, in Figure 6(b) an additional peak was observed.…”
Section: Xps and Ftirmentioning
confidence: 99%
“…Ogaki et al used static (S-) SIMS and gentle (G-) SIMS to extract information on the surface monomer unit distribution of polylactide- co -glycolide materials. They demonstrated that G-SIMS successfully identified the structurally important key fragments leading to direct identification , .…”
Section: Synthesis Of Polymersmentioning
confidence: 99%